1986
DOI: 10.1037/0022-3514.51.5.1032
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral routes to persuasion: An individual difference perspective.

Abstract: According to the elaboration likelihood model, both situational and dispositional factors can influence the extent to which attitudes are formed through issue-relevant thinking. The results of Experiment I indicated that individuals high in need for cognition are more likely to think about and elaborate cognitively on issue-relevant information when forming attitudes than are individuals low in need for cognition. Analyses further indicated that individuals low in need for cognition acted as cognitive misers r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
457
3
20

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 682 publications
(518 citation statements)
references
References 37 publications
20
457
3
20
Order By: Relevance
“…For example, compared to low scorers, high scores have stronger links between their moods and their thoughts (e.g., Petty, Schumann, Richman, & Strathman, 1993), their thoughts and their attitudes (see Cacioppo et al, 1996), and their attitudes and their behaviors (e.g., Cacioppo, Petty, Kao, & Rodriguez, 1986). They report less uncertainty about the nature of cause and effect relationships in the social world (e.g., Weary & Edwards, 1994) and possess more complex schemata for explaining human behavior (Fletcher, Danilovics, Fernandez, Peterson, & Reeder, 1986).…”
Section: Conscientiousnessmentioning
confidence: 99%
“…For example, compared to low scorers, high scores have stronger links between their moods and their thoughts (e.g., Petty, Schumann, Richman, & Strathman, 1993), their thoughts and their attitudes (see Cacioppo et al, 1996), and their attitudes and their behaviors (e.g., Cacioppo, Petty, Kao, & Rodriguez, 1986). They report less uncertainty about the nature of cause and effect relationships in the social world (e.g., Weary & Edwards, 1994) and possess more complex schemata for explaining human behavior (Fletcher, Danilovics, Fernandez, Peterson, & Reeder, 1986).…”
Section: Conscientiousnessmentioning
confidence: 99%
“…83 Additionally, Cacioppo et al argued that '[t]he fact that the situational factors that have been used to manipulate the extent to which attitudes are based on issue-relevant thinking sometimes account for only a small portion of variance is theoretically due, in part, to systematic individual differences among people in their desire to engage in issue-relevant thinking when they formulate their attitudes'. 84 Further, they argued that one of the systematic individual differences is need for cognition and individuals low in need for cognition are cognitive misers. 85 Without measuring or controlling involvement, these researchers 86 examined the persuasion routers travelled by individuals low in need for cognition (cognitive misers) and high in need for cognition (cognitive elaborators) and reported a moderating effect of need-for-cognition on argument quality's influence on attitude.…”
Section: Coding Proceduresmentioning
confidence: 99%
“…It could be suggested that ambivalence covaries with specific personality traits that facilitate systematic processing. For example, people who are ambivalent toward a group might generally possess a higher need for cognition, which is an individual difference variable that has been shown to facilitate systematic processing (e.g., Cacioppo, Petty, Kao, & Rodriguez, 1986;Cacioppo, Petty, & Morris, 1983). To test whether this possible relation might explain our findings, we asked our additional sample of 36 participants to complete measures of need for cognition (Cacioppo, Petty, & Kao, 1984), need for closure (Kruglanski, Webster, & Klem, 1993), and tolerance for ambiguity (McLain, 1993).…”
Section: Alternative Explanations?mentioning
confidence: 99%